Notifikasi Temperatur Lebih Pada Photovoltaic Polycrystalline 100 Wp Berbasis IoT Menggunakan Aplikasi Thinger.io - Armin Sofijan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Abstract Photovoltaic (PV) is a power plant that converts solar radiation into electrical energy through the photovoltaic effect, where the process of generating electrical energy is affected by one factor, that is, an increase in temperature exceed. Excessive temperature rise leads to reduced PV efficiency. More temperature monitoring is required to maintain PV performance, typically, more temperature measurements are constrained by distance, in real time, automatically. The original idea of ​​the author was to use IoT with thinger.io internet application with unlimited remote installation. Thinger.io is an open source platform in IoT used as a user interface or data visualization during monitoring. The monitoring in this study will detect excessive temperature, as well as voltage, current, and solar radiation parameters using an IoT-based application compared to conventional measurements using data loggers. have error rate. The results show that the overheating message only appears when the PV temperature is equal to or above 450C and repeats when the temperature decrease below 450C and then increase again to exceed 450C, the average percentage error is 0.016%, 0.107%, 0.006% and 0.008%.